2017
DOI: 10.1209/0295-5075/117/37005
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in the unusual low-valence layered material LaSrNiRuO 4

Abstract: Introduction. -Transition metal oxides encompass a lot of functional materials due to their varying chargespin-orbital states and the abundant electronic-magneticoptical properties to name a few [1][2][3][4][5][6][7][8]. For example, oxides with mixed 3d-4d-5d transition metals often display various and even unusual charge states [9-14] which arise from the much different chemical potentials of those transition metals. As a result, a special spin-orbital state associated with the unusual charge state could off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…Therefore, we attempt to achieve it in a compromise way, by studying the hypothetic material LaSrNiZnO 4 with a substitution of the nonmagnetic Zn 2+ for the S=0 Ru 2+ . This choice is also justified by the consideration that the Zn 2+ ion (0.74 Å) has a very similar ionic size to the S=0 Ru 2+ (t 6 2g , probably 0.74 Å) which is unavailable but can be extrapolated from the ionic sizes of 0.565 Å/Ru 5+ (t [12]. Here again, we perform hybrid functional PBE0 calculations to verify this finding.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Therefore, we attempt to achieve it in a compromise way, by studying the hypothetic material LaSrNiZnO 4 with a substitution of the nonmagnetic Zn 2+ for the S=0 Ru 2+ . This choice is also justified by the consideration that the Zn 2+ ion (0.74 Å) has a very similar ionic size to the S=0 Ru 2+ (t 6 2g , probably 0.74 Å) which is unavailable but can be extrapolated from the ionic sizes of 0.565 Å/Ru 5+ (t [12]. Here again, we perform hybrid functional PBE0 calculations to verify this finding.…”
Section: Resultsmentioning
confidence: 75%
“…It is not surprising that this AF superexchange in LaSrNiZnO 4 due to the in-plane Ni + x 2 − y 2 orbital is 'stronger' than the AF superexchange in LaSr 3 NiRuO 4 H 4 with the out-of-plane Ni + 3z 2 − r 2 orbital, as the x 2 − y 2 orbital has a larger overlap with the in-plane ligands. It is now clear that the Ni + S=1/2 and Ru 2+ S=0 state can only maintain a very weak AF in LaSrNiRuO 4 as in LaSr 3 NiRuO 4 H 4 , and that this charge-spin state cannot at all yield the actual strong FM in LaSrNiRuO 4 .Our previous LSDA+U calculations have shown that LaSrNiRuO 4 is in the robust Ni + S=1/2 and Ru 2+ S=1 ground state[12]. Here again, we perform hybrid functional PBE0 calculations to verify this finding.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The Ru 2+ (4d 6 ) shows an S = 1 state stabilized by a moderate Hund exchange along with a weak crystal field. 20 If the Ru 2+ ion were in the nonmagnetic S = 0 state as suggested in ref coupling would occur only in the diluted S = 1/2 Ni + sublattice, and it would thus be only weakly AFM due to a superexchange between the well-separated Ni + ions with the half-filled x 2 − y 2 orbital. Clearly, this would contradict the measured T C ∼ 200 K. 19 Starting from these considerations, here, we predict a surprisingly strong FM in the layered insulator Sr 2 NiRuO 4 .…”
Section: Introductionmentioning
confidence: 97%
“…18 Very recently, the Ni−Ruordered LaSrNiRuO 4 was synthesized and found to be an FM layered material with T C ∼ 200 K. 19 The FM order has been explained by considering the superexchange between the unusual low-valence Ni + and Ru 2+ cations. 20 The Ni + (3d 9 ) is in the S = 1/2 state and has an active x 2 − y 2 orbital under the influence of a square planar crystal field. The Ru 2+ (4d 6 ) shows an S = 1 state stabilized by a moderate Hund exchange along with a weak crystal field.…”
Section: Introductionmentioning
confidence: 99%